Coastal Erosion Reduces Resilience and Disrupts Compositional Dynamics of The Mangrove Ecosystem - Irsadi, Andin; Jabbar, Abdul; Dewi, Nur Kusuma; Somantri, Dadang; Khair, Amar Sharaf Eldin; Sidiq, Wahid Akhsin Budi Nur; Mutiatari, Dhita Pracisca; Martuti, Nana Kariada Tri (Biosaintifika: Journal of Biology & Biology Education, 2025)
Indonesia’s coastline, particularly Kendal Regency in Central Java, faces critical mangrove degradation due to land-use changes and rising sea levels. This study aims to asses the condition and erosion impacting Kendal's mangrove ecosystems to inform future conservation strategies. Using remote sensing technology, multi-spatial and multi-temporal imagery from 2005–2023 was analyzed and validated with field observations to evaluate mangrove species composition, structure, and land changes. The mangrove area increased by 52% in three locations, with the Bodri River delta (Pidodo Kulon and Pidodo Wetan villages) showing the most significant growth at 76.69 hectares. Ngebum Beach (Mororejo) had the largest proportional increase, reaching 185%. The ecosystems are moderately diverse, containing at least 11 mangrove species, though Rhizophora dominates due to extensive planting efforts. Despite stable conditions, these ecosystems face threats from deforestation for aquaculture, the primary driver of land erosion, compounded by rising sea levels. Although mangrove areas have expanded significantly, ongoing challenges include erosion, anthropogenic pressures, and limited species diversity. Future strategies must involve multi-stakeholder collaboration to implement sustainable practices, promote species diversity, develop erosion mitigation models, and conduct awareness campaigns to ensure the resilience of Kendal’s mangrove ecosystems.